Interdisciplinary Emergency Care: The Role of Radiology, Pharmacy, Nursing, Laboratory, and Nutrition in Enhancing Patient Outcomes in Crisis Situations - Ali Abdullah Almarzooq,; Abdullah Radattallah Alkhaledi,; Ayed Sulaiman Ayed Alfaidi,; Hala Yahya Sabai,; Dawlah Mohammed Alsheikh,; Nasser Abdullah Saeed,; Saad Mohammed Fayiz,; Asma Ali Yahya Jabbari,; Turki Mubarak Saad Alluwaymi,; Abrar Mater Al.Rehiliy,; Abdulrahman Ali Alshahrani, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Multidisciplinary collaboration lies at the heart of ensuring effective responses in many health emergencies, such as pandemics, natural catastrophes, and the increase in chronic diseases. The contributions of pharmacy, epidemiology, emergency care, and social services to public health programs are unique and clearly distinguished in this analysis. The pharmacy profession has become central to prevention through the provision of health services that are accessible, including prescription management, immunizations, and health screenings. These are particularly useful in underserved areas. In expanding access, pharmacists make possible early diagnosis and continuing care, thuscontributing so substantially to community health. They enable the proper targeting of treatments and distribution of resources, hence an evidence-based response to emerging risks. Emergency care providers are central to frontline health responses, providing rapid assessment, stabilization, and triage in high-pressure situations-a key component in extended health events. Their role of addressing acute situations is paramount in the management of urgent needs in health crises. Social services contribute to the effort of public health by addressing the social determinants of health: housing, food security, and access to mental health.